The Legal Consequences of Constitutional Court Decision 18/PUU-XVII/2019 on Fiduciary Execution in Sharia Financing - Achmad Iftauddin; Rial Fu'adi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study examines how Constitutional Court Decision Number 18/PUU-XVII/2019 reinterprets the legal norms governing the execution of fiduciary guarantees, and how its implications affect the authority of Religious Courts in enforcing the execution of collateral in Sharia-based financing. Employing a statute-based approach, the author conducts a comparative analytical interpretation of relevant laws and regulations on fiduciary guarantee execution and contrasts them with the reinterpretations introduced by the Constitutional Court. The findings indicate that the Decision affirms the equal importance of the principles of freedom of contract, consensualism, and due process of law alongside the principle of legal certainty in contractual arrangements. Consequently, Sharia financing institutions (creditors) may execute collateral objects without the involvement of Religious Courts (parate execution) only under two cumulative conditions: (a) the creditor and debtor have mutually agreed upon clear criteria for default, and (b) the debtor voluntarily surrenders the fiduciary object. In the absence of these conditions, execution must be carried out through the Religious Court. The study concludes that, to enable the Religious Courts to perform executions more effectively and efficiently, immediate updates to procedural law and execution mechanisms are needed through regulations and policies issued by the Supreme Court of the Republic of Indonesia.